Performance of an interprofessional team in the School Health Program: Experience report (Research, Society and Development, 2021)
The present work aims to report the experience of an interprofessional team in the implementation of health education actions to promote healthy eating among public school students, through the Programa Saúde na Escola (PSE), one of the policies developed by the Ministry of Health (MS). This is a qualitative, descriptive, experience report type study. The actions were carried out between the months of July and August 2019 in a municipal school with children from the 1st to the 5th year of elementary school I, during a period of 04 days, totaling 22 classes of the morning and afternoon shift, in the city of Manaus / AM. Throughout the process, it was evident to the team the importance of explicit interprofessional interaction between academics, teachers and health professionals, which made it possible to establish collaborative practices between the professions involved. It was possible to experience one of the mottos of Interprofessional Education in Health (IPE) "learn together to work together through collaborative health practices".